Absence of the TRIP13 c.1060C>T Mutation in Wilms Tumor Patients From Pakistan. Issue 3 (April 2020) - Rashid, Muhammad U.; Naeemi, Humaira; Qazi, Abid Q.; Muhammad, Noor; Ahmad, Mansoor; Akhtar, Noreen; Rahman, Nazneen
Abstract : Background and Aim: Wilms tumor (WT) is the most common childhood malignant renal tumor. Germline mutations in several WT predisposition genes have been identified. However, the fundamental cause of most WT patients remains unexplained. Recently, a founder mutation, c.1060C>T (p. Arg254X) in a mitotic spindle checkpoint gene, TRIP13, was reported in 5 unrelated children with WT from the United Kingdom, of Pakistani descent from Azad Kashmir region. This observation suggests other children with WT in Pakistan may also harbor this mutation. We conducted the first study to assess the contribution of TRIP13 c.1060C>T mutation to WT in Pakistan. Materials and Methods: Constitutional genomic DNA from 68 Pakistani individuals including unrelated WT cases (n=26) and one (n=10) or both (n=32) of their parent(s) were screened for the TRIP13 c.1060C>T mutation using DNA sequence analysis. We also included positive controls in the analyses. Results: The median age of WT diagnosis was 3.0 years (range, 0.75 to 10). The TRIP13 c.1060C>T mutation was not found in any WT patient (n=26) or their parents (n=42). Twenty-four patients (92.4%) presented with unilateral tumor and 2 patients (7.7%) were diagnosed with synchronous bilateral WT. Thirteen patients (50%) reported parental consanguinity. Thirteen patients (50.0%) belonged to the Punjabi ethnicity and 1 patient (3.8%) had a Kashmiri background. Four patients (16.7%) reported a family history of WT or other malignancies. The predominant histologic subtype was stromal (46.2%). The majority of patients presented with >5 cm of tumor size (81%). None of the patients had a personal or family history of congenital anomalies, or associated genetic syndromes. Conclusions: Our findings suggest that TRIP13 c.1060C>T mutation may be infrequent in Pakistani WT cases. Further evaluation of this mutation in a large number of WT patients of Kashmiri heritage and various ethnic backgrounds from Pakistan is warranted.